Characterizing instrumentation canister aerodynamics on the FAAM BAe-146-301 atmospheric research aircraft - Bennett, Christopher J.; Nott, G. J.; Wellpott, A.; Lawson, Nicholas J.; Delise, M.; Woodcock, B.; Gratton, Guy (American Society of Civil Engineers (ASCE), 2019)
A computational fluid dynamics (CFD) investigation was aimed at accurately predicting the air flow characteristics in the vicinity of underwing-mounted instruments on the Facility for Airborne Atmospheric Measurement’s (FAAM) BAe-146-301. Perturbation of the free stream airflow as it passes through the region of detection of the underwing instruments may lead to additional uncertainties in the measurement of clouds and cloud particles. The CFD model was validated with flight data from an Aircraft-Integrated Meteorological Measurement System (AIMMS-20) in a wing-mounted instrument canister. Flow predictions showed a consistent slowing from the true air speed of the aircraft in the longitudinal direction and the introduction of horizontal and vertical flows up to 10% of the air speed. The potential impact of these flow perturbations on sizing of particles with cloud imaging probes was modeled. Sizing errors were dependent on the methodology used and the shape of the particle; those due to transverse flows remained very small but mis-sizing due to unaccounted longitudinal flow perturbations were potentially more serious.